1988
DOI: 10.1111/j.1600-0609.1988.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in myeloproliferative disorders: Characterization and sequential studies show multiple platelet abnormalities, and change with time

Abstract: Bleeding and thrombosis are well known major causes of morbidity and mortality in patients with myeloproliferative disorders (MPD) but the relationship between these clinical events and the commonly found platelet function abnormalities have not been established. In this study we performed simultaneous laboratory evaluations in 54 patients with MPD to investigate abnormalities in platelet aggregation and cyclooxygenase activity, the latter by using an in vitro aspirin inhibition test; the studies were repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…46,47 Most functional studies on MPN platelets have been performed by measuring in vitro platelet aggregation in response to various stimuli. 48 In spite of the intrinsic limitation of the technique, aggregation measurements have provided some interesting findings such as the phenomenon of spontaneous aggregation 49 and the reduced platelet response to some aggregating agents such as adenosine diphosphate collagen and epinephrine. 46 In PV and ET platelets, multiple abnormalities of membrane glycoproteins (Gps) and receptors have been reported.…”
Section: Platelet Functional Abnormalitiesmentioning
confidence: 99%
“…46,47 Most functional studies on MPN platelets have been performed by measuring in vitro platelet aggregation in response to various stimuli. 48 In spite of the intrinsic limitation of the technique, aggregation measurements have provided some interesting findings such as the phenomenon of spontaneous aggregation 49 and the reduced platelet response to some aggregating agents such as adenosine diphosphate collagen and epinephrine. 46 In PV and ET platelets, multiple abnormalities of membrane glycoproteins (Gps) and receptors have been reported.…”
Section: Platelet Functional Abnormalitiesmentioning
confidence: 99%
“…With regard to ADP-induced aggregation, previous studies have shown conflicting results with either a minority (18,19) or a majority (16, 17) of PV patients showing an abnormal response. In this study, there was no significant difference between patients and controls in ADP-induced aggregation even though the results were seen to vary more than those with PMA as the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that the absence of aggregation response was related to past history of thrombotic or hemorrhagic complications (60), whereas others did not find such a relationship (61); following therapy, abnormalities in platelet aggregation response frequently improved (61,63). One study demonstrated that the two paradoxical abnormalities of platelet hyperfunction and hypofunction may co-exist in a significant proportion of patients, and that platelet function can and does change with time in some, with platelet hypofunction being the only constant abnormality (65). The pathophysiologic and molecular defects that account for acquired platelet function defects as seen in MPD are still poorly understood.…”
Section: Platelet Morphology and Reactivitymentioning
confidence: 99%